1990
DOI: 10.3891/acta.chem.scand.44-0603
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Various 1,1-Dihalo-2-haloalkylcyclopropanes and 1,1,2-Trihalocyclopropanes and their Reduction to Dihalides using Tributyltin Hydride.

Abstract: Fifteen members of the title compounds such as (III), (VII) or (X) are prepared by dihalocarbene addition to the corresponding alkenes, and their reduction behavior toward Bu3SnH is investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Estimated yield of 9 was 0.21 g, 57%. The spectral data were in accordance with the literature [37].…”
Section: Discussionsupporting
confidence: 71%
“…Estimated yield of 9 was 0.21 g, 57%. The spectral data were in accordance with the literature [37].…”
Section: Discussionsupporting
confidence: 71%
“…Either addition of CBr 3 − or of :CBr 2 can be achieved specifically; 17 the similar addition of :CCl 2 has also been reported. 18 Pd-catalyzed ethoxycarbonylation of methallyl bromide (NaOEt-Na 2 PdCl 4 -[(Ph 2 P) 2 CH 2 ] 2 at rt) is also readily achieved. 19…”
Section: (2) (3) Sph Phs Phsmentioning
confidence: 99%
“…This product contained one carbon atom more than the starting material, which clearly indicated that 1 had been formed, but had suffered ring-opening in a subsequent reaction. And sure enough, when the reaction was repeated with no ethanol present, cyclopropane 1 was the only product obtained, and furthermore, when 1 was treated with 50 % NaOH/TEBA/EtOH (8 equiv), ring-opening took place [3] (Scheme 1). However, it then appeared that 2 was not the only product formed; in addition, a ketal, viz.…”
Section: Introductionmentioning
confidence: 99%